Managed care improves prognosis in AMI patients irrespectively of the hospital setting. Data from the MAnaged Care for Acute Myocardial Infarction Survivors (MACAMIS) Programme. (25th November 2020) - Jankowski, P; Topor-Madry, R; Gasior, M; Ceglowska, U; Teisseyre, P; Ciesla, D; Wisniewska, A; Gryka, P; Wysoczanski, W; Zdrojewski, T
Abstract: Background: In 2017 a nation-wide system of managed care for MI survivors comprising acute treatment of MI, cardiac rehabilitation and cardiac ambulatory care within one year following MI was implemented in Poland. The managed care programme (MCP) was proved to be related to lower risk of all-cause death. The goal of the analysis was to assess the effectiveness of MCP in patients discharged from university, district, municipal and non-public hospitals. Methods: The database of survivors of acute MI discharged from hospital from October 1, 2017 to December 31, 2018 was analyzed. Patients who died within 10 days after discharge were excluded from the analysis. The primary end-point was defined as death from any cause. Propensity-Score Matching using nearest neighbor matching was used to form comparable groups of patients participating and not participating in the MCP. The Cox proportional hazard regression analysis was used to assess the relation between MCP and the overall mortality. Results: MCP was implemented in the first stage in 48 hospitals spread around the country (about 34% of all hospitals treating acute MI patients in Poland). Among them 14 were university, 20 district, 8 municipal and 6 nonpublic hospitals. Out of 34064 patients discharged from hospitals with MCP implemented 10404 patients (30.5%) participated in MCP. They were matched with 10404 patients not participating in the MCP. About 24% of the analyzed patients were discharged from university hospitals, 42% from district hospitals, 20% from nonpublic, 14% from municipal and other hospitals. During 326.3±134.8 days of follow-up 1062 patients died (4.4% vs. 6.5% of patients participating and not participating in the MCP; p<0.001). Hazard ratios related to MCP of patients hospitalized in each hospital categories are presented in the table. Conclusion: The implemented in Poland nation-wide system of managed care for MI survivors is related to improved survival in all hospital settings. Funding Acknowledgement: Type of funding source: None